PORTFOLIO INVESTMENTS IN THE SELECTED EUROPEAN TRANSITION ECONOMIES - Bartókova, Ľudmila (Journal of Advanced Studies in Finance, 2011)
Nowadays, economies are closely linked together by their trade and financial cross border transactions as well as capital flows. Considerable deepening of financial integration during 1990s together with gradual liberalization of international capital flows contributed to overall increase in capital transactions. This paper analyzes inflows and outflows of particular capital category, i.e. foreign portfolio investments in selected transition countries of European Union. The analysis compares and explains inflows and outflows of investments in both equity and debt securities for Slovak Republic, Czech Republic, Hungary, Poland, Bulgaria and Romania.